RINGKASAN HASIL PENELITIAN MIGRASI TRANSNASIONAL DAN IDENTITAS DIASPORA DI KOTAKOTA PERBATASAN DI ASIA TENGGARA STUDI KASUS THAILAND DENGAN MYANMAR DAN LAOS - Amorisa Wiratri; Betti Rosita Sari; Yekti Maunati; Lamijo Lamijo (Jurnal Kajian Wilayah, 2017)
This research has done in the border cities in Southeast Asia, namely Thailand, Lao PDR and Myanmar that straight bordered with China. Border cities are strategic locations for transnational migration, including the mobility of human, goods, information and transfer of ideas, where at the same time also contributed as bridge that linked between two or three different countries in Southeast Asia. China’s economic expansion and people migration from neighbouring countries has influenced the dynamic of economic, social and culture for people who live in border areas, especially in North Thailand. This research focus on the process of transnational migration, the identity of diaspora, and small scale economic activity among diaspora groups in border areas between north Thailand and Myanmar and also Lao PDR.Keywords:  transnational migration, diaspora identity, border citiesAbstrakPenelitian ini dilakukan di kota-kota perbatasan Asia Tenggara, yaitu Thailand, Laos, dan Myanmar yang berbatasan langsung dengan China. Kota perbatasan merupakan lokasi strategis bagi pergerakan transnasional baik manusia, barang, informasi, dan ide-ide, sekaligus sebagai wilayah yang menghubungkan antara dua atau tiga negara yang berbeda di Asia Tenggara. Ekspansi ekonomi China dan pergerakan manusia dari negara-negara tetangga mempengaruhi dinamika ekonomi, sosial, dan budaya masyarakat di perbatasan. Fokus penelitian ini adalah menggali proses migrasi transnasional, identitas budaya diaspora, dan aktivitas ekonomi skala kecil kelompok diaspora di wilayah perbatasan Thailand utara dengan Myanmar dan Laos.Kata Kunci: migrasi transnasional, identitas budaya diaspora, kota perbatasan